(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Euphemism is the subject of the linguocultural studies. Nowadays euphemistic expressions are widely studied in all aspects of the language. The article reveals the feature of euphemisms in proverbs and sayings in Uzbek and English languages. The comparative analyses of the two languages’ euphemized proverbs and sayings showed that the negative characters of people are shown periphrastically by animals, which illustrate the Uzbek and English people’s mentality, world outlook, customs.